PENGARUH ORAL MOTORIC THERAPY TERHADAP PENINGKATAN REFLEKS HISAP PADA BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI RUANG PERINATOLOGI RS WAVA HUSADA MALANG - Lilis Sulistya Nengrum (Health Care Media, 2024)
Low birth weight (LBW) babies are those who are born weighing less than 2500 grams. One of the issues that arise in LBW babies is the weakness of the sucking and swallowing reflex, which increases the risk of drinking disorders, which will eventually interfere with the baby's growth and development. Oral motor therapy is one of the therapies used to improve the sucking reflex in infants. The purpose of this study was to see how oral motor therapy affected on increasing the sucking reflexes in LBW babies in the Perinatology Room of Wava Husada Hospital in Malang. This study is a pre-experimental design with a one-group pre-post test. The observation sheet is used as a measuring tool. The Mann-Whitney test was used in this study as a statistical test. The findings revealed that 28 LBW babies (100%) had a weak sucking reflex before oral motor therapy and 22 LBW babies (79%) had a strong sucking reflex after oral motor therapy. The Mann Whitney test results showed a P-Value (0.000) < (0.05), indicating that the hypothesis was accepted, namely that there was an effect of oral motor therapy on increasing the sucking reflex in LBW babies treated in the Perinatology Room at Wava Husada Hospital Malang.